2010
DOI: 10.26719/2010.16.4.434
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among clinical dental students at Jordanian universities

Abstract: Dentistry is a profession demanding physical and mental efforts as well as people contact, which can result in burnout. The level of burnout among 307 clinical dental students in 2 Jordanian universities was evaluated using the Maslach Burnout Inventory survey. Scores for the inventory's 3 subscales were calculated and the mean values for the students' groups were computed separately. Dental students in both universities suffered high levels of emotional exhaustion and depersonalization. The dental students at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 10 publications
1
52
0
Order By: Relevance
“…Although some stress is inherent in dentistry and education and is likely beneficial as a learning stimulus (2), there is a concern that high levels of stress and prolonged stress exposure may precipitate burnout, a term that describes the experience of long-term work-related exhaustion and diminished interest (3). Although burnout among practicing dentists is typically considered a 'professional syndrome' (4)(5)(6)(7)(8)(9)(10), some evidence indicates that manifestations of burnout may be prevalent and can be detected among dental students (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Although some stress is inherent in dentistry and education and is likely beneficial as a learning stimulus (2), there is a concern that high levels of stress and prolonged stress exposure may precipitate burnout, a term that describes the experience of long-term work-related exhaustion and diminished interest (3). Although burnout among practicing dentists is typically considered a 'professional syndrome' (4)(5)(6)(7)(8)(9)(10), some evidence indicates that manifestations of burnout may be prevalent and can be detected among dental students (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Interest in identifying burnout amongst predoctoral dental students has increased in many countries over the years. [7][8][9][10][11][12] Depression during dental education is also a concern. One study reported the prevalence of depression in dental students in Spain and found that it was higher in the second and fourth years of training compared to the fifth year.…”
mentioning
confidence: 99%
“…The dentistry field is both physically and mentally demanding, and when added to personal contact with patients, it can lead to BOS 8 . Dentists are the health professionals most affected by BOS, where factors such as weather and organizational issues, coupled with existing activity demands, interpersonal roles and their ambiguity, among others, are all factors that generate and/or trigger emotional exhaustion 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Dentists are the health professionals most affected by BOS, where factors such as weather and organizational issues, coupled with existing activity demands, interpersonal roles and their ambiguity, among others, are all factors that generate and/or trigger emotional exhaustion 9 . Moreover, BOS has been associated with drops in productivity, reduced quality of treatment delivery, intention to leave work 10 and a tendancy to avoid contact with people, including colleagues, patients, friends and family 8 .…”
Section: Introductionmentioning
confidence: 99%